Perspectives of healthcare providers and persons with type 2 diabetes mellitus on improving glycaemic control in Kinshasa, Democratic Republic of the Congo: a qualitative study - Joel M Francis; Olufemi Babatunde Omole; Jean-Pierre Fina Lubaki (BMJ Public Health)
Introduction Glycaemic control remains suboptimal in the Democratic Republic of the Congo. Defining interventions to improve glycaemic control requires a clear knowledge of factors driving poor glycaemic control. Qualitative studies exploring the perspectives of key stakeholders on this issue are lacking in the Democratic Republic of the Congo. This study aimed to explore the perspectives of persons with type 2 diabetes and healthcare providers on ways to improve glycaemic control in Kinshasa, Democratic Republic of the Congo.Methods This qualitative study used face-to-face, semistructured interviews on 26 purposively sampled participants: 10 persons with type 2 diabetes and 16 healthcare providers. The study used deductive, constructionist and thematic analyses. Themes were organised and integrated using the WHO Innovative Care for Chronic Conditions Framework.Results The healthcare providers recommended better preparation of the healthcare system for better care of diabetes. This is achieved through training of healthcare providers, equipping healthcare structures and organising a reliable drug delivery system. Healthcare providers must also act to ensure that patients get adequate support from their surroundings and the community by providing adequate information about diabetes. The policy environment must create conditions for alleviating the cost of care and prevention of diabetes. In addition, patients with diabetes identified three needs: need mainly for financial support to overcome the cost of diabetes, knowledge for better self-management of the illness and support from healthcare providers to succeed in self-management.Conclusion Improving glycaemic control in persons with type 2 diabetes requires multidimensional strategies, with particular focus on empowering patients and their families for efficient self-management, strengthening the healthcare system for diabetes care and greater involvement of the government in terms of funding and adopting positive policies. To be efficient, these interventions need to be integrated into the chronic diseases management framework.